Growth and survival of spat, juveniles and adult Akoya pearl oyster Pinctada imbricata fucata (Gould, 1850) in different rearing conditions and stocking densities - Rinju, R. Mary; Anil, M.K.; Williams, E. Sherly (Indian Journal of Fisheries, 2020)
Growth trials were conducted using hatchery produced spat of Pinctada imbricata fucata (Gould, 1850) having average dorso-ventral measurement (DVM) of 3.99 mm, hinge length (HL) 3.94 mm, thickness (THK) 1.25 mm and weight (WGT) 0.008 g. The first experiment was a comparative growth assessment of spat grown in one ton FRP tanks in the hatchery and with that of spat reared in micron meshed cages  under open sea conditions for a period of three months. During the third month, spats grown in micron meshed cages showed growth increments  of 7.83 mm (DVM), 4.86 mm (HL), 1.61 mm (THK) and 0.192 g (WGT) whereas those grown in FRP tanks grew only by 0.95 mm (DVM), 0.5 mm (HL), 0.46 mm (THK) and 0.004 g (WGT) indicating faster growth in open sea conditions.  Second experiment was conducted to elucidate the effect of stocking density on the growth and survival of juveniles  reared in plastic baskets at different stocking densities viz., 200 (0.03 nos. cm-3) 300 (0.049 nos. cm-3), 400 (0.065 nos. cm-3), 500 (0.08 nos. cm-3), 600 (0.098 nos. cm-3), 700 (0.11 nos. cm-3), 800 (0.13 nos. cm-3), 900 (0.14 nos. cm-3)  and 1000 (0.16 nos. cm-3) numbers  per basket.   Results indicated that P. imbricata  fucata juveniles can be grown at stocking densities of up to 400 per basket for a period of five months with 90% survival without much reduction in growth. Third experiment was conducted on the growth of  P. imbricata  fucata  subadults in box cages at different stocking densities viz.,  200 (0.006 nos. cm-3), 300 (0.01 nos. cm-3), 400 (0.013 nos. cm-3), 500 (0.016  nos. cm-3), 600 (0.02 nos. cm-3), 700 (0.023 nos. cm-3), 800 (0.026 nos. cm-3), 900 (0.03 nos. cm-3)  and 1000 (nos. cm-3)   numbers per cage. Survival rates ranged from 98.5 to 98.6% at stocking densities up to 400 per cage during the fifth month without any significant variation in the DVM, HL and THK of oysters.Keywords: Box cages, Growth, Physico-chemical parameters, Pinctada imbricata fucata, Plastic baskets